Start & manage your own business a smart and practical guide for new entrepreneurs - Sanchez, Marlo (Malate, Manila, Philippines De La Salle University Press, Inc., 1998)
Purpose: To share key ideas on how to successfully establish, manage and develop a small business enterprise.
Entrepreneurship -- Business Organizations -- Business Legislations -- Franchising -- Environmental scanning -- Business Plan (Financing) -- Budgeting and Forecasting -- Time and Motion studies -- Marketing -- Social Responsibility -- Businesses (Listing)
Includes index.
Keywords: Entrepreneurship -- Handbook, manuals, etc; New business enterprises -- Handbooks, manuals, etc; Business -- Handbooks, manuals etc